GUEREÑA, J. L., Ruiz BERRIO, J., y TIANA FERRER, A. (dirs.) (1994). Historia de la educación contemporánea. Diez años de investigación. - Bernabé Bartolomé Martínez (Universidad Complutense de Madrid, 1995)
Sin resumen